Citrullinated vimentin mediates development and progression of lung fibrosis - Fu Jun Li; Ranu Surolia; Huashi Li; Zheng Wang; Gang Liu; Tejaswini Kulkarni; Adriana V. F. Massicano; James A. Mobley; Santanu Mondal; João A. de Andrade; Scott A. Coonrod; Paul R. Thompson; et al. (2021)
Cd/CB-induced citrullinated vimentin promotes PAD2- and TLR4-dependent lung fibrosis.